2019
DOI: 10.1007/s00044-019-02463-w
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and antiprotozoal activity of 3-acetyl-2,5-disubstituted-1,3,4-oxadiazolines: a review

Abstract: In the last 20 years there has been a significant increase in interest in the structure of oxadiazole derivatives, especially 3-acetyl-1,3,4-oxadiazolines. It is known that these derivatives possess: antibacterial, antifungal, antitubercular, antiprotozoal, anticancer and anti-inflammatory activity. Therefore, many medicinal chemists choose 3-acetyl-1,3,4oxadiazoline scaffold for the synthesis of new potentially active substances with a better effectiveness and less toxicity. This article is a literature revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Various oxadiazole derivatives are subjected to synthesis under microwave irradiation, and their biological activities are reported that include antibacterial, antifungal, antiviral, anticonvulsant, antitumor, antimalarial, antitubercular, anti-asthmatic, antidepressant, antidiabetic, antioxidant, antiparkinsonian, analgesic and antiinflammatory, etc. ( Figure 6 ) [ 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Microwave-assisted Synthesis Of Biologically Active Oxadimentioning
confidence: 99%
“…Various oxadiazole derivatives are subjected to synthesis under microwave irradiation, and their biological activities are reported that include antibacterial, antifungal, antiviral, anticonvulsant, antitumor, antimalarial, antitubercular, anti-asthmatic, antidepressant, antidiabetic, antioxidant, antiparkinsonian, analgesic and antiinflammatory, etc. ( Figure 6 ) [ 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Microwave-assisted Synthesis Of Biologically Active Oxadimentioning
confidence: 99%
“…Bearing in mind the above-mentioned problems, we conducted a literature review that showed that 3-acetyl-1,3,4-oxadiazoline derivatives constitute the class of compounds with high biological potential [8]. A simple method of the synthesis and a broad spectrum of activity make them an intensively studied group [9].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, antibacterial [11][12][13][14][15][16], antifungal [17][18][19][20], anticancer [21][22][23], antimycobacterial [24][25][26][27] and antiprotozoal [28,29] effects of 1,3,4-oxadiazoles have been documented. Currently, there are no registered medicines with an acetyl substituent in the 1,3,4-oxadiazole ring, but there are medicines with an 1,3,4-oxadiazole moiety, such as Furamizole, Nesapidil, Zibotentan, Raltegravir or Tiodazosin [8]. The introduction of an acetyl group in the third position of the 1,3,4-oxadiazole ring seems to be an interesting solution, especially with regard to the fact that many studies showed that it can induce antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research conducted in our group has revealed that 3-acetyl-2,5-disubstituted-1,3,4-oxadiazolines show significant bioactivity [ 8 , 9 ]. These derivatives have a broad spectrum of activity mainly: antibacterial [ 10 , 11 , 12 , 13 , 14 , 15 ], antifungal [ 16 , 17 , 18 , 19 ], antitubercular [ 20 , 21 , 22 ], antiprotozoal [ 23 , 24 ], anti-cancer [ 25 , 26 , 27 , 28 ], antioxidant [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of the antibacterial action of 1,3,4-oxadiazoles may result from the presence of the –N=CO group in their structure and the transcription of genes involved in biofilm formation, such as SARA (regulator of gene expression), icaA (polysaccharide intercellular adhesion (PIA) or polymeric N -acetylglucosamine (PNAG) production), spa (surface protein for bacterial aggregation), fnbA (fibronectin-binding protein A) and fnbB (fibronectin-binding protein B). The gene necessary for biofilm formation in S. aureus as well as the main global regulator of the diverse range of virulence determinants in S. aureus [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%